2020
DOI: 10.21203/rs.3.rs-94543/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glucose Transporter 1 and Hypoxia-Inducible Factor 1α is Indicators of Head and Neck Squamous Cell Carcinoma Aggressiveness and Poor Prognosis: A Case Control Study

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is a common and aggressive malignancy with a high morbidity and mortality profile. Increased levels of expression of the tumor hypoxia markers, hypoxia-inducible factor 1α (HIF-1α) and glucose transporter 1 (GLUT-1), are indicators of poor prognosis in carcinoma.Materials and methods: This study involved detection of HIF-1α and GLUT-1 expression with a mean follow-up period of 10 years in 69 cases of HNSCC (23 cases of hypopharyngeal carcinoma and 46 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…The molecule association of Ki67 and macroautophagy is controversial. Different authors have shown that positive Beclin1 expression is associated with a higher Ki67 index, indicating that high Beclin1 expression may lead to cellular proliferation [56][57][58]. However, some other studies have failed to find this relationship [59].…”
Section: Macroautophagy and Pituitary Tumorsmentioning
confidence: 99%
“…The molecule association of Ki67 and macroautophagy is controversial. Different authors have shown that positive Beclin1 expression is associated with a higher Ki67 index, indicating that high Beclin1 expression may lead to cellular proliferation [56][57][58]. However, some other studies have failed to find this relationship [59].…”
Section: Macroautophagy and Pituitary Tumorsmentioning
confidence: 99%